Factors contributing to the prevalence of sexually transmitted diseases among youth in Nansana Town Council, Wakiso District. A cross-sectional study. - Setuba, Emily; Nakafu, Teopista; Nalubega, Jane Frank; Immaculate Naggulu Posperia; Akankwasa, Edith; Okello, Elizabeth; David Kavuma (Student’s Journal of Health Research Africa, 2025)
Background In Uganda, STDs remain a pressing public health issue among the youth, with an estimated prevalence of 49% among youth. This study aimed to assess the factors contributing to the prevalence of sexually transmitted diseases (STDs) among youths in Nansana Town Council, Wakiso District. Methods A descriptive cross-sectional study design was employed, utilizing quantitative methods for data collection. Over 8 days, 72 youth were selected using a simple random sampling method. A structured questionnaire was used to collect data, and it involved closed-ended questions. The data collected was analyzed manually, and after the findings were entered into a Microsoft Excel 2013, that was then presented in the form of tables, pie charts, and graphs. Results Out of the 72 participants sampled, more than half (52.8%) were aged between 24 and 29 years, and half (50%) had attained secondary level education. Individual factors, more than half (51.4%) had two sexual partners, more than half (54.2%) never used condoms during sexual activity, and nearly half (48.6%) engaged in sexual activity after alcohol use a few times. Concerning Health facility factors, more than half (59.7%) disagreed that health workers are always present, more than half (59.7%) strongly disagreed that recommended drugs were readily available, and most (66.7%) disagreed that health facilities are close to their homes. About social and cultural factors, half (50%) stated that their partners encouraged sexual behavior, and 77.8% indicated that talking about sex and STDs was considered taboo. Conclusion The prevalence of STDs was attributed to multiple sexual partners, occasional sex under the influence of alcohol, and low condom use. Recommendation There is a need to enhance public health education through continuous community sensitization campaigns on the importance of consistent condom use, STD testing, and the risks associated with multiple sexual partners and alcohol-influenced sexual activity.